Multiplicity of Solutions for Gradient Systems Using Landesman-Lazer Conditions - Edcarlos D. da Silva (Abstract and Applied Analysis)
We establish existence and multiplicity of solutions for an elliptic system which presents resonance at infinity of Landesman-Lazer type. In order to describe the resonance, we use an eigenvalue problem with indefinite weights. In all results, we use Variational Methods, Morse Theory and Critical Groups.